Application of fluorescence based molecular assays for improved detection and typing of Brucella strains in clinical samples - Kiril Krstevski; Ivancho Naletoski; Dine Mitrov; Slavcho Mrenoshki; Iskra Cvetkovikj; Aleksandar Janevski; Aleksandar Dodovski; Igor Djadjovski (Macedonian Veterinary Review, 2015)
Bacteria from the genus Brucella are causative agents of brucellosis – a zoonotic disease which affects many wild and domestic animal species and humans. Taking into account the significant socio-economic and public health impact of brucellosis, its control is of great importance for endemic areas. The chosen control strategy could be successful only if adapted to the current epidemiological situation. This implies that a choice of appropriate diagnostic procedures for detection and typing of Brucella spp. strains are of essential importance. Significant advancement of molecular techniques and their advantages compared to classical methods, give strong arguments in promotion of these techniques as a powerful tool for comprehensive diagnostics of brucellosis. Considering this, the major tasks of the study were to select and implement molecular tests for detection and genotyping Brucella spp. and evaluate their performances using DNA from cultivated brucellae (islolates) and limited number of tissue samples from seropositive animals. The obtained results confirmed that implemented real time PCR for Brucella spp. detection, as well as MLVA-16 used for genotyping, have excellent analytical sensitivity (4.2 fg of Brucella DNA were successfully detected and genotyped). Furthermore, compared to bacteriological cultivation of Brucella spp., real time PCR and MLVA-16 protocols showed superior diagnostic sensitivity and detected Brucella DNA in tissues from which Brucella could not be cultivated. Based on the summarized study results, we propose a diagnostic algorithm for detection and genotyping of Brucella spp. bacteria. Routine use of proposed diagnostic algorithm will improve the effectiveness of infection confirmation and help for accurate evaluation of epidemiological situation.